Implementasi Shalat Dhuha Dalam Meningkatkan Karakter Religius Siswa di MAN 1 Padang Lawas - Sinar Nasution; Yulianisa Yulianisa (Yayasan Rahmat Islamiyah, 2023)
This study aims to find out how the Dhuha Prayer is implemented in improving the religious character of students at MAN 1 Padang Lawas. The type of research in this thesis is qualitative research, which places more emphasis on the analysis of the inference process inductive. The approach used by the author is a descriptive approach, The situation described in this study is the implementation of Duha prayer in improving the religious character of students at MAN 1 Padang Lawas. Data collection was carried out by conducting observations, interviews, documentation. Data analysis using data reduction analysis, data presentation, as well as drawing conclusions. The results of this study indicate that through the implementation of Duha prayer, students will have a better understanding of the importance of Duha prayer as a recommended sunnah practice. They will realize the benefits and virtues of this dhuha prayer in enhancing their relationship with Allah and strengthening spiritual bonds. The school principal and teachers have provided education about the procedures for Dhuha prayer, its virtues, and provided motivation to students. With a good understanding, students will be motivated to carry out Duha prayers regularly and with high awareness. Principals and teachers are exemplary examples in carrying out Dhuha prayers. By seeing their consistent Dhuha prayer practice, students will be inspired and motivated to follow it.